Impact of COVID‐19‐related social restrictions on orthopaedic trauma in a level 1 trauma centre in Sydney: the first wave. Issue 1 (13th October 2020) - Probert, Annabel C.; Sivakumar, Brahman S.; An, Vincent; Nicholls, Sarah L.; Shatrov, Jobe G.; Symes, Michael J.; Ellis, Andrew M.
Abstract : This study examines the impact that social distancing measures introduced to combat coronavirus disease 2019 (COVID‐19) have had on the orthopaedic trauma load at a level 1 trauma hospital in Sydney. Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has affected communities worldwide. This study examines the impact that public health measures to control viral spread have had on orthopaedic trauma presenting to an Australian level 1 trauma centre. We hypothesized that the volume of orthopaedic trauma in the period of social distancing would decrease, and the mechanisms of injury differ, compared to pre‐pandemic times. Methods: We performed a retrospective analysis of patients requiring emergency orthopaedic surgery between 16 March and 21 April 2020 (the period after social distancing and lockdown commenced), and compared it to the group of patients from the same period in 2019. We collected demographic data, as well as injury type, anatomical location, mechanism of injury and surgical logistics. Results: During the COVID‐19 period, total emergency operations performed decreased by 15.6% compared to the same period in 2019. Orthopaedic admissions decreased by 30.8%. Demographics of the groups were unchanged. Anaesthetic time decreased, but total time spent in the operating theatre was unchanged. Road trauma comprised a similar proportion of cases overall; however, cycling‐related accidents increased significantly, making up 11% of presentations during COVID‐19. Sporting injuries, work‐related injuries and multi‐traumas reduced during the pandemic. Conclusion: The impact of COVID‐19‐related lockdown measures and social distancing on orthopaedic trauma in Australia has been an overall decrease in volume of cases, combined with significant changes in the mechanisms of injury necessitating surgery.